Fish disease study of Asian seabass (Lates calcarifer) in a floating marine cage: Endoparasite and blood profile - DEWI HIDAYATI; ANNISAA RIZQI NURINDRA; NURLITA ABDULGANI; EDWIN SETIAWAN; NOVA MAULIDINA; NUR SYAHRONI; YEYES MULYADI (Society for Indonesian Biodiversity, 2021)
Abstract. Hidayati D, Nurindra AR, Abdulgani N, Setiawan E, Maulidina N, Syahroni N, Mulyadi Y. 2021. Fish disease study of Asian seabass (Lates calcarifer) in a floating marine cage: Endoparasite and blood profile. Biodiversitas 22: 4505-4511. The Indonesian government has multiple targets and priority programs to increase aquaculture productivity in 2021. Hence, the development of mariculture commodities such as Asian seabass (Lates calcarifer) in one of the potential coastal areas, Sendang Biru, is strategic. However, sustainable productivity needs good management, including the health monitoring of fish. This study aimed to determine the condition of seabass under mariculture in a floating cage in Sendang Biru, Malang, Indonesia. Thirty seabass (Lates calcarifer) from 0 to 60 days after stocking age (ASE) were taken from a Sendang Biru floating cage. Blood and intestine samples were taken five times from day 0 to day 60 ASE. Blood samples were carried out through the caudal vein and observed using a hemocytometer. Endoparasite analysis was performed by fish intestine examination from the anterior intestine to the posterior rectum. Pseudoterranova and Diphyllobothrium were found with 10% and 3.33% prevalence, respectively. The intensity of Pseudoterranova was one individual/fish, and that of Diphyllobothrium was 2.33 individuals/fish. The highest mean of total erythrocyte count (TEC) found in 0 day ASE was at the level of 0.82±0.55×106 cells/mm3, and the lowest was found in 60 days ASE (0.51±0.24×106 cells/mm3). The highest mean of total leucocyte count (TLC) was 9.20±3.69x104 cells/mm3, at day 0, and leukocyte levels tended to decrease until day 60 ASE (7.74±3.43×104 cells/mm3). Overall, despite the TEC and TLC tending to decrease from 0 to 60 days ASE, in statistically indicated no significant differences in TLC at different ASEs (p > 0.05). The hematological profile indicated the health statuses of the cultured Asian seabass in the current study were in a condition of anemic and infected.